How Occupation Is Taught and Assessed in Occupational Therapy Education: A Scoping Review. - Taff, Steven D.; Pitonyak, Jennifer S.; Krishnagiri, Sheama; Price, Pollie (American Journal of Occupational Therapy)
Importance: Because occupation is the core concept of the profession, it is imperative that students have deep knowledge of the various facets of occupation and how it serves as both therapeutic mode and objective for clients. Despite the importance, how occupation is taught and assessed is not well understood. Objective: To identify existing literature and gaps in professional dialogue surrounding how knowledge of the concept of occupation is taught and assessed. Method: The Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guided this review. Data Sources: Electronic databases included PubMed/MEDLINE, Embase, Scopus, Web of Science, PsycINFO, and CINAHL. Study Selection and Data Collection: The study explored peer-reviewed publications from 1993 to 2023 and included articles that met the following criteria: occupational therapy or occupational science is represented; the concept of occupation is present; and teaching, learning, or assessment of occupation is described. Data extraction points included perspective of occupation evoked in teaching/learning, knowledge about occupation represented in teaching/learning, and instruction and assessment strategies represented. Findings: A total of 54 articles were included for final data extraction. Occupation as a way of seeing practice was the most common educational perspective, teaching of occupation as a concept unto itself and separate from practice was very prominent, and experiential learning was a frequently occurring instructional approach. Conclusions and Relevance: Educators need to deepen their knowledge about occupation and intentionally use authentic instructional approaches that foster student learning in transformative ways. Plain-Language Summary: This review explored literature that describes or investigates how knowledge about the profession's core concept of occupation is taught and assessed. The articles included for final review discussed multiple perspectives of occupation, recognized teaching of occupation as independent of therapy as the most common, identified experiential learning as the main teaching strategy, and noted that assessment of occupation was much less represented. Results of the review indicate a need for educators to be more knowledgeable about occupation and to create more authentic, transformative learning experiences to strengthen student knowledge about occupation. This review explored literature that describes or investigates how knowledge about the profession's core concept of occupation is taught and assessed.